CLIMATE CHANGE DETECTION WITH EXTREME WEATHER FACTORS CONCERNING ALGERIA - Benaïchata, L.; Mederbal, K.; Chouieb, M. (European Scientific Journal, ESJ, 2015)
In order to detect if our area is affected by a climatic tendency, a great number of indices was calculated on the basis of daily data from the Algerian meteorological service network. The maps analysis of the indices trend calculated using RclimDex, illustrated a significant change in the climatic parameters. Thirty statistical indices were selected among the twenty seven proposed by ETCCDI team. The calculation of these indices is based on maximum and minimum daily temperatures and precipitations data. The temperature indices showed warming tendency. Unexpectedly, we noticed a positive trend with the precipitation indices over the north ouest of Algeria.